Accessing New Chemical Entities through Microfluidic Systems. Issue 23 (6th May 2014) - Rodrigues, Tiago; Schneider, Petra; Schneider, Gisbert
Abstract Flow systems have been successfully utilized for a wide variety of applications in chemical research and development, including the miniaturization of (bio)analytical methods and synthetic (bio)organic chemistry. Currently, we are witnessing the growing use of microfluidic technologies for the discovery of new chemical entities. As a consequence, chemical biology and molecular medicine research are being reshaped by this technique. In this Minireview we portray the state‐of‐the‐art, including the most recent advances in the application of microchip reactors as well as the micro‐ and mesoscale coil reactor‐assisted synthesis of bioactive small molecules, and forecast the potential future use of this promising technology.